Indonesia Rancang bangun aplikasi absensi mahasiswa menggunakan metode Viola Jhones algoritma HaarCascade di UIM - Lukman Syahrul Gunawan; Busro Akramul Umam; Masdukil Makruf (Energy - Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
Recognition of human facial images is one of the main technologies that continues to be developed. In the field of Computer Vision in its application in biometric recognition systems, search systems, indexing of digital video databases, limited area access control security systems, video conferencing, human-computer interaction. and so forth. The Viola-Jones method is an object detection method that has a fairly high accuracy of about 93.7% with a speed 15 times faster than the Rowley Baluja-Kanade detector and about 600 times faster than the Schneiderman-Kanade detector. The Haar Cascade Classifier algorithm is one of the algorithms used to detect a face. Cascade Classifier is used to record attendance with facial recognition which can record students in real-time. Kata Kunci: face detection, OpenCV, Haar cascade